Characterization of Convective Plumes Associated With Oceanic Deep Convection in the Northwestern Mediterranean From High‐Resolution In Situ Data Collected by Gliders. Issue 12 (13th December 2017) - Margirier, Félix; Bosse, Anthony; Testor, Pierre; L'Hévéder, Blandine; Mortier, Laurent; Smeed, David
Abstract: Numerous gliders have been deployed in the Gulf of Lions (northwestern Mediterranean Sea) and in particular during episodes of open‐ocean deep convection in the winter 2012–2013. The data collected represents an unprecedented density of in situ observations providing a first in situ statistical and 3‐D characterization of the important mixing agents of the deep convection phenomenon, the so‐called plumes. A methodology based on a glider‐static flight model was applied to infer the oceanic vertical velocity signal from the glider navigation data. We demonstrate that during the active phase of mixing, the gliders underwent significant oceanic vertical velocities up to 18 cm s −1 . Focusing on the data collected by two gliders during the 2012–2013 winter, 120 small‐scale convective downward plumes were detected with a mean radius of 350 m and separated by about 2 km. We estimate that the plumes cover 27% of the convection area. Gliders detected downward velocities with a magnitude larger than that of the upward ones (−6 versus +2 cm s −1 on average). Along‐track recordings of temperature and salinity as well as biogeochemical properties (dissolved oxygen, fluorescence, and turbidity) allow a statistical characterization of the water masses' properties in the plumes' core with respect to the "background": the average downward signal is of colder (−1.8 × 10 −3 °C), slightly saltier (+4.9 × 10 −4 psu) and thus denser waters (+7.5 × 10 −4 kg m −3 ). The plunging waters are also on average more fluorescent (+2.3 × 10 −2 μg L −1 ). The plumes are associated with a vertical diffusion coefficient of 7.0 m 2 s −1 and their vertical velocity variance scales with the ratio of the buoyancy loss over the Coriolis parameter to the power 0.86. Key Points: From a glider flight model, we extract for the first time the statistical physical and biogeochemical characteristics of convective plumes Intense vertical velocities are observed (up to 18 cm s −1 ) and the plumes are found to cover about one third of the deep convection area Vertical velocities scaled by atmospheric fluxes inducing downward buoyancy fluxes with a vertical diffusion coefficient of 10 m 2 s −1